2013
DOI: 10.1093/europace/eut190
|View full text |Cite
|
Sign up to set email alerts
|

CHADS2 and CHA2DS2-VASc scores to predict morbidity and mortality in heart failure patients candidates to cardiac resynchronization therapy

Abstract: In CRT-D patients, pre-implant CHA2DS2-VASc score is an independent predictor of major clinical events at 30-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 33 publications
1
44
0
2
Order By: Relevance
“…40 Paoletti Perini et al mentioned that CHA 2 DS 2 -VASc score is an independent predictor of major clinical events at 30-month follow-up in patients with HF. 16 Thus, we speculated the hypothesis that higher CHA 2 DS 2 -VASc scores may be associated with worse prognosis in patients with APE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Paoletti Perini et al mentioned that CHA 2 DS 2 -VASc score is an independent predictor of major clinical events at 30-month follow-up in patients with HF. 16 Thus, we speculated the hypothesis that higher CHA 2 DS 2 -VASc scores may be associated with worse prognosis in patients with APE.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, potential clinical use of CHA 2 DS 2 -VASc score in patients with HF and coronary artery disease (CAD) has been shown. 16,17 Several reports suggest that there is a close association between components of the CHA 2 DS 2 -VASc score and risk of VTE. [18][19][20][21][22][23][24][25] From this point of view, we speculated the hypothesis that higher CHA 2 DS 2 -VASc scores might be associated with risk of mortality in patients with APE.…”
Section: Introductionmentioning
confidence: 99%
“…HF and AF share common risk‐factors, and the occurrence of either of them may induce the onset of a vicious circle which, in turn, facilitates the manifestation of the other 16. Although the CHADS 2 and CHA 2 DS 2 ‐VASc score series are predictors of stroke in AF patients,3 their predictivity has recently extended beyond their original field as follows: (1) ischemic stroke in patients with coronary artery disease without AF,17 (2) mortality, recurrences of stroke, and major cardiovascular events in stroke patients without AF,18 (3) mortality in stroke survivors with or without AF,19 (4) hospitalization for cardiovascular causes in AF patients,20 and (5) HF hospitalization and cardiac death in HF patients who underwent cardiac resynchronization therapy 21. In addition, it has been recently reported that CHA 2 DS 2 ‐VASc score was associated with not only thromboembolic complications but also mortality in patients with HF 22.…”
Section: Discussionmentioning
confidence: 99%
“…Шкала CHA 2 DS 2 -VASc позволяет прогнозировать заболеваемость и смертность у пациентов с сердеч-ной недостаточностью и показаниями для сердечной ресинхронизирующей терапии [27]. Шкалы оценки тяжести внебольничной пневмонии успешно приме-нялись у пациентов с госпитальной пневмонией [28].…”
Section: шкалы могут использоваться в оценке прогноза других заболеванийunclassified